Technological aspects of constructing 3D-model of engineering structures in the cities of the RF Arctic Region - Evgeny Ilyich Avrunev; Aleksandr Viktorovich Chernov; Aleksey Viktorovich Dubrovsky; Aleksandr Vladimirovich Komissarov; Elena Yurievna Pasechnik (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
The relevance of the research is caused by the necessity to develop 3D cadastral register in the cities with complex multilevel structure of engendering constructions. Currently, the development of optimal structure of the cadastral register, its standardization and opportunity of being used not only to control landproperty relations but to solve the other important scientific and engineering issues as well, is the direction in development of geodesic and cadastral science. The aim of the research is to propose the algorithm for forming 3D-model required to construct 3D land cadaster in the cities, especially for those located in the arctic region, as the buildings and engineering constructions in the permafrost zone may suffer from sufficient sediments and deformations, which determine the probability of occurrence of construction limit stress state. Subject of the research: the engineering structure model. Methods: mathematical modeling. Results. The authors have proposed to develop additionally the deformation certificate for a certain engineering construction, suffering from sufficient sediments and deformation, including the constructions being in the permafrost zone. They proposed as well the cadastral information obtained to put into appropriate sections of the Unified State Register of Immovable Property. The conditions determining the necessity of developing the local 3D model of engineering constructions were proved. The paper introduces the criteria which allow selecting the optimal coordinate system and structure for constructing the local 3D model, which may include the deformation certificate of the object. The authors derived the equations for calculating the required accuracy in geodesic measurements owing to the prescribed root-mean-square errors of the 3D model elements of the engineering construction. The mathematical algorithm was developed. Based on the algorithm one can calculate the required accuracy of geodesic measurements owing to the proposed accuracy parameters for constructing 3D model of engineering structure.